Nonlinear Adaptive Controller for Speed Control in Induction Motor Drives - Jasmin, M.; Philomina, S.; Virgin, G. Angelo (International Journal of Psychosocial Rehabilitation, 2018)
Induction motor is widely used in small scale aswell as the large scale industries. In industrial sector, there prevails a major drawback in speed controlling of three phase induction motor drives when subjected to heavy loads. These are called as disturbances in a motor. A motor can have both the internal disturbance as well as the external disturbance. To eliminate this types of disturbance many controller where implemented with fast computing algorithm. To reduce the computation time and also to get a minimum overshoot with respect to the changes in the state transient variables, a three first order Auto Disturbance Rejection Controller (ADRC) is used for evaluating the squirrel cage induction motor drive co-ordinates (d-q) as well as to regulate the speed of the motor under disturbances. It is clear that the control scheme of ADRC is much feasible and effective when compared to conventional controllers.